PENINGKATAN PENDAPATAN MASYARAKAT DESA PASIRUKEM MELALUI INTEGRASI BUDIDAYA IKAN LELE SISTEM BIOFLOK DAN DIVERSIFIKASI PRODUK OLAHAN - Wulandari, Yeni Sari; Sam’un, Mohamad; Suherman, Enjang (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2026)
Community empowerment through the development of the fisheries sector is one of the strategies to improve the welfare of rural communities. This community service activity was conducted from August to November 2025 in Pasirukem Village, Cilamaya Kulon District, Karawang Regency, involving approximately 22 participants consisting of fish farming groups and food processing groups. The activity aimed to enhance community capacity through the application of biofloc-based catfish farming technology and the diversification of processed catfish products. The method used was a participatory approach, which included preparation, focus group discussions (FGD), socialization, training, mentoring, as well as monitoring and evaluation. The activities carried out included the construction of biofloc ponds; training on catfish cultivation; training on processing products into nuggets, roulade, shredded catfish, and crispy catfish; as well as training on business management and digital marketing. The results of the activity showed an increase in the partners’ knowledge, as indicated by the improvement in post-test results compared to the pre-test, with the average initial score of 17.67% increasing to 100% after the training activities. In addition, the partners were able to practice processing catfish into several value-added products as an effort to diversify fisheries-based products. This activity is expected to serve as an initial step in developing sustainable catfish farming and processing enterprises in Pasirukem Village.Pemberdayaan masyarakat melalui pengembangan sektor perikanan merupakan salah satu strategi untuk meningkatkan kesejahteraan masyarakat pedesaan. Kegiatan pengabdian kepada masyarakat ini dilaksanakan pada bulan Agustus–November 2025 di Desa Pasirukem, Kecamatan Cilamaya Kulon, Kabupaten Karawang dengan melibatkan sekitar 22 peserta yang terdiri dari kelompok pembudidaya ikan dan kelompok pengolah produk pangan. Kegiatan ini bertujuan untuk meningkatkan kapasitas masyarakat melalui penerapan teknologi budidaya ikan lele sistem bioflok serta diversifikasi produk olahan ikan lele. Metode yang digunakan adalah pendekatan partisipatif yang meliputi tahap persiapan, focus group discussion (FGD), sosialisasi, pelatihan, pendampingan, serta monitoring dan evaluasi. Kegiatan yang dilakukan meliputi pembangunan kolam bioflok, pelatihan budidaya ikan lele, pelatihan pengolahan produk menjadi nugget, rolade, abon, dan lele krispi, serta pelatihan manajemen usaha dan pemasaran digital. Hasil kegiatan menunjukkan adanya peningkatan pengetahuan mitra yang ditunjukkan oleh peningkatan hasil post-test dibandingkan dengan pre-test, dengan rata-rata nilai awal sebesar 17,67% meningkat menjadi 100% setelah kegiatan pelatihan. Selain itu, mitra juga mampu mempraktikkan pengolahan ikan lele menjadi beberapa produk olahan sebagai upaya diversifikasi produk berbasis perikanan. Kegiatan ini diharapkan dapat menjadi langkah awal dalam pengembangan usaha budidaya dan pengolahan ikan lele yang berkelanjutan di Desa Pasirukem.